The political dynamics of managing The Kelutap Bersatu Joint Village – owned enterprise (BUMDes Bersama) in Kelam Permai Sub-District, Sintang District, West Kalimantan - Situmorang, Asri Kurniati; Mahrawa, Faisal Andri (Privietlab, 2025)
The passing of Law Number 6 of 2014 on villages has opened up new opportunities for villages to manage their economic resources on their own, including forming BUMDes. However, the management of BUMDes is actually shaped by local political factors and complex power dynamics. This study explores how power functions within the management of BUMDes Bersama and how these practices affect village governance and community participation. This study used a qualitative approach using a case study method. Data was gathered through in-depth interviews, observation, and document analysis. The theories applied include Local Politics and Regional Autonomy theory, Michel Foucault's Power Relations theory, and the Good Governance theory. The results show that, although BUMDes aim to improve the welfare of village communities through the collective management of economic businesses, local political intervention changes the function of this institution. Political actors utilize BUMDes to gain political support by directing facility assistance to the farmer groups that support them. This practice causes BUMDes to lose neutrality and reduces community trust in the institution. On the other hand, BUMDes management becomes less transparent, with decision-making dominated by certain parties, without inclusive involvement of all elements of the community.